Prof Miles Padgett (OBE, FRS) from blue-sky research to real-world applications and challenges - Ruidong Xia; Ying Hu (Light: Science & Applications)
Editorial Orbital angular momentum (OAM) research has evolved from a theoretical concept to a tool with diverse applications. Early advancements distinguished OAM from spin angular momentum (SAM), leading to practical innovations such as optical tweezers and quantum entanglement. Compared with SAM, OAM can carry more information, which makes it invaluable for high-capacity data transmission and secure communications. Professor Miles Padgett, a leading scientist in the field of optical momentum, is well-known for his contributions, including the realization of an optical spanner for spinning micron-sized objects, the use of orbital angular momentum to increase the data capacity for communication systems, and the development of an angular form of the Einstein‒Podolky‒Rosen (EPR) quantum paradox. In an enlightening conversation with Light: Science & Applications, he highlighted the fundamental properties of the angular momentum of light, the invention of optical tweezers and optical spanners, and the demonstration of OAM states for extending the alphabet of optical communication using both classical and quantum light. In particular, he explained the various aspects of OAM distinguished from SAM. This interview further explored his collaboration with industry partners that bridges the gap between academic research and real-world applications by using his skill in light shaping in various areas, including his current role as the principal investigator for QuantIC and his group’s work on building novel endoscopes that are the size of the width of a human hair. As an academic administrator, during his 5-year term as Vice-Principal for Research at the University of Glasgow (2014–2019), Professor Miles Padgett’s efforts led to an improvement in the quality of the University’s research publications from the lower quartile to the upper quartile in the Russell Group of the UKs leading universities. In this interview, he shared his approach to improve research culture to build up research collaboration, secure external funding for conducting cutting-edge research, and translate blue-sky research into real-world impact. In addition to his research success, Miles also serves many important roles for research societies and funding agencies. For example, as the Interim Executive Chair for EPSRC in 2023, his tenure successfully led to a nearly 50% increase in the number of funded Centres for Doctoral Training, corresponding to an additional intake of 1500 students. When asked about his motivation to serve on research committees, he expressed his ambition to shape the direction of science, advocating for areas of science with the potential to impact society. For young scientists, his advice is to understand that perseverance and adaptability are crucial for research career progress while remembering that luck also plays a role—sometime you just have to hang on in.